Stakeholders’ knowledge, attitude, and practices in relation to minimizing aflatoxins contamination in peanut-based products - Mohd Azaman, Nur Nazurah (2017)
Aflatoxins are carcinogens produced by Aspergillus flavus and A. parasiticus that commonly found in agricultural commodities particularly peanut and occurring found in human foods and animal feeds. Aflatoxins are one of the food contaminants, which have been the important issues and reported widely in many developing countries such as India and China. However, the issues on aflatoxins are still new among food stakeholders in Malaysia. Health issues that affect to human and animals take place almost every day. Unfortunately, only a few people know about the effects and risks from aflatoxins contamination to human health. Knowledge of the danger of aflatoxins contamination in peanuts-based products is still lacking among food stakeholders. The government of Malaysia concerned on the health issues that have been increasing these days relating to aflatoxins. Therefore, both public and private agencies have taken several steps to increase their surveillance and investigation towards only good quality of imported peanuts will reach to the Malaysian markets. Thus, the objective of this study was to determine the food supply chain stakeholders’ knowledge, attitude, and practices (KAP) in relation to minimizing aflatoxins contamination in peanut-based products.